(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Ms. Karen Ronsayro was operating as a sole proprietor in 2014 at Coruna Street Village East Cainta Rizal and offered accounting services. Yet, not everything functions perfectly. In 2019, Ms. Ronsayro and her father, Mr. Rey Osea, founded ORAS Accounting Services at 4 Lawin Street in Novaville, Caloocan City. The company changed its name to Osea Ronsayro Accounting Services and started providing auditing, tax filing, registration or permit, and bookkeeping services. Orientation, observation, demonstration, training, and application systems are used for their training system. They carry out the tasks assigned to them. An accounting staff member needs to possess certain qualities, including integrity, honesty, and dependability. Professionalism and confidentiality should also be top priorities. This study was designed to assist in developing an intervention program by extending and putting into practice a formal ethical code of conduct. This study aims to evaluate the effectiveness of an intervention program at ORAS Accounting Services in producing employees who are progressive and fit to work for a certain job or career as a result. This study revealed that there is no significant difference between the assessment of Male and Female groups of respondents in the Extent of Implementation of a Formal Ethical Code of Conduct in terms of rules, expectations and management, company policies to help compliance, Guidelines for Behavior, and Day-to-day business practices. This was confirmed by the t-computed value of 1.0730, which is less than the t-critical value of 3.707 at 0.01 level of significance and 6 degrees of freedom. With these compared values, the null hypothesis is Accepted. The Proposed Intervention Program includes the key Result Area on rules expectation and management, company policies to help compliance, Guidelines for Behavior, and Day-to-day business practices. Other areas included in the intervention program were as follows: Objective, Program of Activity, Person Involved, Time Frame, Budget, Monitoring, and Evaluation.